Place-based approaches to improve the mental health and wellbeing of children and young people: a rapid realist review - Anna March; Kate Allen; Karuna Davies; Julie Harris; Alison Bethel; Laura Kennedy; Tamanna Malhotra; Rachael Stemp; Bianca Alexandrescu; Tim Hobbs; Peter Fonagy; Steve Pilling; et al. (Systematic Reviews)
Abstract Background Adolescent mental health continues to be a pressing public health concern across the globe, in spite of renewed efforts in recent years to improve mental health and wellbeing outcomes. With many mental health services and systems ill-equipped to meet young people’s needs, there is growing evidence that prevention interventions addressing the social and structural determinants of mental health should be prioritised. Consequently, there is a move away from isolated interventions towards ‘place-based approaches’ that aim to unlock systemic or structural change. However, there is limited evidence on how these approaches create change and the different contextual factors or underlying mechanisms that influence outcomes. This is the first realist review on place-based approaches to improve young people’s mental health. Methods This rapid realist review synthesises relevant literature on place-based approaches to improve the mental health and wellbeing of children and young people. The review involved consultation with programme developers, an expert panel of content specialists and a Young Person’s Advisory Group. Online databases were searched for peer-reviewed and grey literature published between January 2000 and August 2023, resulting in 5685 articles. Results Fifteen articles from eight countries were included in the review, from which 11 realist context-mechanism-outcome configurations (CMOCs) were developed to explain the underlying mechanisms present in the place-based approaches. These CMOCs were categorised into three themes: (1) Building relationships and trust, (2) bringing a social determinants lens, and (3) educating and empowering community stakeholders. Conclusions This review provides valuable insights into the mechanisms underpinning place-based approaches. However, the mechanisms identified primarily address the intermediate outcomes of place-based approaches, such as engaging the right stakeholders and creating opportunities for youth voices to be heard. Articles did not address the challenges around long-term sustainability and there remain crucial questions around the pathway to wider systemic change. Recommendations are included for future development and evaluation of place-based approaches to improve young people’s mental health. Systematic review registration PROSPERO CRD42023450778.